2015
DOI: 10.5937/tehmesa1501001t
|View full text |Cite
|
Sign up to set email alerts
|

Intense light pulses upset the sensory quality of meat products

Abstract: A b s t r a c t: Intense light pulses (ILP) is a promising non

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There were no statistically significant differences in any of the attributes evaluated between 1-pulse treated and untreated samples of Parma ham 7 . In the case of bacon, the same treatment caused significant difference only in odor, although assessors noted that the odor of both, treated and control bacon samples, was not so pronounced.…”
Section: Five-point-scale Scoring Methodsmentioning
confidence: 45%
See 2 more Smart Citations
“…There were no statistically significant differences in any of the attributes evaluated between 1-pulse treated and untreated samples of Parma ham 7 . In the case of bacon, the same treatment caused significant difference only in odor, although assessors noted that the odor of both, treated and control bacon samples, was not so pronounced.…”
Section: Five-point-scale Scoring Methodsmentioning
confidence: 45%
“…The lightness of dry-cured loin also endured, while it was significantly higher in salchichón (fermented sausage) in samples treated with 11.9 J/cm 2 as reported by Ganan et al 12 . The a* value significantly decreased after the 5-pulses treatment in Parma ham, fermented sausage and bacon while the b* value significantly increased only in bacon 7 . It has been reported that when cured meat products are exposed to light, discoloration appears as a decrease in a* values and an increase in b* values, with or without a change in L* 16 .…”
Section: Instrumental Color Measurementmentioning
confidence: 84%
See 1 more Smart Citation
“…Sensory analysis was performed by a simple descriptive method (Radovanović & Popov-Raljić, 2000). When describing sensory properties of Herzegovinian dry smoked goat meat, the most frequent and appropriate descriptive terms were used (Stamenković & Dević, 2006). The sensory evaluation was performed by a three-member expert commission that performs evaluations for fairs and exhibitions.…”
Section: Methodsmentioning
confidence: 99%